The Balkan Wars, 1912-1913 prelude to the First World War - Hall, Richard C. (Warfare and history, 2000)
Richard Hall examines the origins, the enactment and the resolution of the Balkan Wars, during which the Ottoman Empire fought a Balkan coalition of Bulgaria, Greece, Montenegro and Serbia